PENGARUH BUDAYA KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SUKABUMI - Susanti, Aty; Rukayat, Yayat; Fajar, Fitriani (Indonesian Journal of Strategic Management, 2025)
This study aims to test whether there is an influence of work culture and work environment on employee performance. This study is a quantitative study with as many as 32 people as a sample who are employees of the National and Political Unity Agency. The sampling method used is a saturated sampling technique with a population of 32 people. The data analysis method used is the multiple linear regression analysis method using the SPSS (Statistical Package for the Social Sciences) version 26 program. The test results show that work culture and work environment have a significant effect on employee performance